Religious Moderation in Fighting Terrorism and Radicalism - Wahid, Annisa; Kuswana, Dadang (Jurnal Iman dan Spiritualitas, 2024)
Indonesia is ranked 37th in terms of the highest terrorism cases globally. A series of successive events since the 2000s. Of course, it causes a lot of losses, not only material but also the psychological and mental health of people who are worried about the safety of their lives. This study aims to find out how to counteract radicalism and terrorism in Indonesia. The method used in this research is library research and analyzed using qualitative analysis techniques. The results of this study indicate that the diversity of religions makes people's anxiety about the existence of terrorism even more complex. Islam, in particular, is increasingly cornered and has a negative view. However, even so, individuals who have an obligation to protect this country synergize in preventing the growth of radicalism on a global scale. Assisted by the government, which is expected to ensure the realization of a just, prosperous, and prosperous society. The presence of religious moderation is a mediator between diversity, where followers of religions can take a middle way amidst the diversity of interpretations of tolerance but still adhere to the essence of their religious teachings.